Mastruz and Rapadura : Folk Communication and Gender in the Bitter Life of Margarida Maria Alves (Revista Internacional de Folkcomunicação, 2025)
This article discusses the topic of the relationship between eco-agro-feminism and folk communication in the life of the rural unionist Margarida Maria Alves. The objective is to observe the presence of elements of folk communication within Gender studies in the context of rural women worker unionists, based on the daily life of Margarida Maria Alves. Methodologically, it is a study from the perspective of folk communication and Gender, addressing the close relationship with the daily life of rural women, in which documentary research and semi-structured interview were used. As initial results, it was possible to expand discussions around folk communication and eco-agro-feminism present in the mystical life of the unionist Margarida Alves in Alagoa Grande-PB.